ANALISIS PENILAIAN ASESMEN NASIONAL BERBASIS KOMPUTER TERHADAP KEMAJUAN PENDIDIKAN DI INDONESIA - Manggaranti; Sri Sumartiningsih; Agus Yuwono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to find out how computer-based national assessments assess educational progress in Indonesia, This research uses a qualitative method with a literature study approach The data collection technique is in the form of books, notes and journal articles, while the data analysis technique uses content analysis techniques which focus on actual content and internal media features. The research results show Transformation of the education evaluation system from the National Examination (UN) to a more comprehensive (ANBK). Positive adaptation of Indonesian education to technological developments, with a shift from paper-based to computer-based systems. The suitability of ANBK with efforts to develop the 4C (Critical Thinking, Communication, Collaboration, Creativity) competencies needed in the era of the industrial revolution. The implication of this research is The implementation of the Computer-Based National Assessment (ANBK) in the education evaluation system in Indonesia has a number of important implications. In terms of educational practice, ANBK demands strengthening technological infrastructure in schools and increasing digital competence for teachers and students. From the perspective of policy makers, regular monitoring and evaluation as well as efforts to equalize access to technology are crucial. In the research realm, studies of the impact of ANBK on learning quality, comparative research with evaluation systems in other countries, as well as the development of more comprehensive technology integration models need to be carried out to optimize the effectiveness and sustainability of the education evaluation system in Indonesia